Optimisation Models for Medium-Long Term Logistics Planning in Mining - Phangestu, Jimmi (Curtin University, 2017)
In the mining industry, the logistics planning problem involves a mining value chain that comprises stockpiles at multiple mines, a rail network, stockpiles at multiple ports, and shipping. The objective is to maximise the total material throughput subject to a range of operational and capacity restrictions. We develop and implement an effective computational model for solving this difficult large-scale problem. Testing on real case studies demonstrates the value of our methodology.